Unveiling Pekon Way Empulau's Tourism Potential: West Lampung Youth's Creative Training in Destination Promotion - Vito Frasetya; Dhanik Sulistyarini; Abdul Firman Ashaf; A Riza Faizal (FOUNDAE (Foundation of Advanced Education), 2022)
West Pesisir Regency has tourist attractions that are not yet widely known, both domestically and internationally. One area with great tourism potential is Pekon Way Empulau Ulu, West Lampung, which boasts the natural beauty of highlands, beaches, and a rich cultural heritage. The aim of this community service activity is to empower local youth through creative content creation training as an effort to promote the tourism potential of the region. The method used in this service involves intensive training on creating and packaging attractive digital content for social media, such as photos, videos, and creative narratives. The results of the training showed an improvement in the youth's skills in producing effective promotional content. This activity also raised awareness among the youth about the importance of technology in advancing local tourism. Its implications are that this activity is expected to increase tourists' awareness of Pekon Way Empulau Ulu's tourism potential and encourage local economic growth through broader promotion on social media. Furthermore, ongoing collaboration between the youth and local government is necessary to maintain the momentum of tourism development.